REZEKNE SEZ – 20 YEARS OF ACHIEVEMENT AND FUTURE CHALLENGE - Ežmale, Sandra (Via Latgalica, 2017)
Rēzekne Special Economic Zone (RSEZ) was established in 1997 as state stock company in order to promote trade, develop production and transport, as well as import and export of goods through Latvia. RSEZ administers state aid in form of tax allowances. During the 20 years of the history of RSEZ several substantial changes have taken place, determining overall development of RSEZ. In 2004 the legal status of the organization was changed due to amendments in legal acts of Latvia. It was reformed from a non-profit organization into a stock company. The ministry of Economics of the Republic of Latvia handed over its stocks of RSEZ to Rēzekne city; subsequently from 2004 to 2010 55% of the stocks were owned by Rēzekne City Council. Regardless of the fact that the control interest was owned by public institutions, RSEZ was a subject of private law and that contradicted the aim of the establishment of RSEZ i. e. promotion of regional development. It determined the necessity to make changes in the functioning of RSEZ. As a result the legal status of RSEZ was changed again in 2010 from stock company to joint municipal institution and amendments with regard to the territory of RSEZ were made. Simultaneously with the aforementioned transitions the economic and politic situation in the country changed – in 2004 Latvia became a member state of the European Union and harmonization of legal acts was performed in accordance with the requirements of the EU. Since 2004 several times substantial amendments have been made in the legal acts regulating the operation of RSEZ and overall its competitiveness and attractiveness for the investments has decreased. Nevertheless the last five years had been the most successful since the establishment of RSEZ. It is possible to distinguish two stages in the development of RSEZ 1) 1997–2010; 2) 2010 – up to nowadays. Altogether RSEZ enterprises (since 2001) have invested almost 150 million euros, from which 120 million euros had been invested in last 10 years and 80 million euros – in last 5 years. The turnover of RSEZ enterprises in 2016 was 84.5 million euros (70.5 million euros – in 2015). In comparison with 2009 the turnover of RSEZ enterprises has increased by 60 million euros or more than 3 times. In the recent years prospects of growth and investment attraction in Latvia and Europe are encumbered by political instability and slow economic growth of Eurozone. Certainly an important factor for investment attraction is developed and qualitative business infrastructure. Therefore significant is the role of the initiatives of municipalities related to implementation of EU Structural Fund financed projects in RSEZ territory as well as proactive work of RSEZ in investment attraction. The paper describes the RSEZ regulatory framework, activities and results achieved in the past, as well as future challenges. The research has been based on the database of RSEZ business research and analysis information system, as well as on the European Union and Latvian policy and development planning documents, laws and regulations. It was found that the RSEZ results and performance indicators have improved after the change of the legal status of RSEZ in 2010. RSEZ enterprises make an important contribution to the development of Rēzekne city and Rēzekne region.